Mitochondrial phosphoglycerate mutase 5 uses alternate catalytic activity as a protein serine/threonine phosphatase to activate ASK1. - Takeda, K.; Komuro, Y.; Hayakawa, T.; Oguchi, H.; Ishida, Y.; Murakami, S.; Noguchi, T.; Kinoshita, H.; Sekine, Y.; Iemura, S.; Natsume, T.; Ichijo, H. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Phosphoglycerate mutase (PGAM) is an enzyme of intermediary metabolism that converts 3-phosphoglycerate to 2-phosphoglycerate in glycolysis. Here, we discovered PGAM5 that is anchored in the mitochondrial membrane lacks PGAM activity and instead associates with the MAP kinase kinase kinase ASK1 and acts as a specific protein Ser/Thr phosphatase that activates ASK1 by dephosphorylation of inhibitory sites. Mutation of an active site His-105 in PGAM5 abolished phosphatase activity with ASK1 and phospho-Thr peptides as substrates. The Drosophila and Caenorhabditis elegans orthologs of PGAM5 also exhibit specific Ser/Thr phosphatase activity and activate the corresponding Drosophila and C. elegans ASK1 kinases. PGAM5 is unrelated to the other known Ser/Thr phosphatases of the PPP, MPP, and FCP families, and our results suggest that this member of the PGAM family has crossed over from small molecules to protein substrates and been adapted to serve as a specialized activator of ASK1.